Understanding preference heterogeneity in electricity services: The case of domestic appliance curtailment contracts - John A. Curtis; William Brazil; Jason Harold (The Economic and Social Research Institute (ESRI), 2019)
Various demand side mechanisms are advocated to reduce peak electricity loads, including direct load control, which comprises remotely shifting load to peak periods. Empirical evidence across several electricity markets reveals heterogeneous customer preferences for these and other electricity service offerings but relatively little is understood concerning the drivers of this preference heterogeneity. Using a discrete choice experiment examining the potential role of domestic appliance curtailment contracts as a means of shifting load, this paper investigates potential drivers of preference heterogeneity with respect to electricity services. Among the research findings are that almost 4-in-5 customers engage with the proposition of appliance curtailment contracts within the context of the survey environment. Customers that previously switched electricity supplier are among those more likely to consider curtailment contracts. From a policy perspective the results highlight the potential of appliance curtailment contracts as a tool to manage peak loads, as well as, the nature of preferences with respect tocurtailment contract attributes. The research also finds that there is no substantial association between either the usual socio-demographic characteristics (e.g., education, etc.) or attitudes to environmental sustainability and preferences for various attributes of appliance curtailment contracts (e.g. appliance type, frequency of curtailment, opt outs, etc.). The absence of such a relationship makes it more difficult to forecast demand, to plan for infrastructure, and to design and market appliance curtailment contracts to customers.
Keywords: 330; demand side management; direct load control; load shifting; preferences; behaviour; attitudes